Analisis Perbedaan Antara Pembiayaan Leasing Konvensional dan Syariah (Ijarah) - Pasi, Kurnia Utami; Fitra, Teguh Haikal; Batubara, Maryam (Ikatan Da'i Indonesia, 2023)
The current economic condition continues to develop, the existence of this leasing company is engaged in financing to help provide capital goods to business owners by way of leasing. There are two financing techniques offered to leasing companies, namely financial leasing and operative leasing. In the form of sharia, this leasing transaction is called ijarah. The principle used by ijarah transactions is based on a contract or agreement. The method used in this research is a literature study by collecting several sources of data related to the topic. The purpose of this study is to review the comparison between the two concept. There are differences in the practice of leasing and ijarah and all provisions on leasing that are prohibited by the syariah concept will be described in this study.